INFORMATION-MEASURING SYSTEM FOR EVALUATION OF ELECTROMAGNETIC RADIATION POWER LEVELS INFLUENCE TO ITS WEAKENED BY PROTECTIVE SHIELDS - O. V. Boiprav; L. M. Lynkov; T. V. Borbotko (Приборы и методы измерений)
An information-measuring system and realized on the basis of its methodology used for evaluation of electromagnetic radiation power levels passing via the protective shielding construction are described. It’s proposed to use the developed methodology for the testing of electromagnetic radiation shields for anechoic chambers